ASSESSMENT OF METERED DOSE INHALER TECHNIQUE IN PATIENTS WITH CHRONIC LUNG DISEASE AT GOVERNMENT HOSPITALS OF RAWALPINDI - Baqai, Haider Zaigum; Saleem, Muhammad Amer; Abair-ul-Haq, Muhammad (Journal of Ayub Medical College Abbottabad, 2011)
Background: Metered dose inhalers (MDIs) are an affective modality of treatment for fast relief from asthma flare-ups and other symptoms, and are often used by asthmatic athletes. It has got lots of benefits and some drawbacks depending on usage technique. With proper technique and training drawbacks can be minimised. The objective of this study was to assess the metered dose inhaler technique in patients with chronic lung disease at government hospitals of Rawalpindi. Methods: A cross-sectional study was conducted in three government hospitals of Rawalpindi. The inhalation technique was assessed in six steps. Results: Clear evidence showed that only 24% patient could perform all the steps correctly. Percentages of people that followed individual steps properly were: preparation (87.5%), exhalation (53.85%), lip closure (68.27%), inhalation (56.73%), breath-holding (27.88%) and puff interval (36.54%). Conclusion: This study showed that a number of patients in government hospitals of Rawalpindi were unable to use metered-dose-inhaler properly and therefore indicates the need to make people aware of this technique either by counselling or arranging seminars. KEYWORDS: chronic lung disease, asthma, metered-dose inhaler.